The Art of Dealing With Anxiety The Catwalk Model Using MUA Services to Apply Stage Makeup - Sakti, Asri Wibawa (Universitas Pendidikan Indonesia, 2021)
The article aims to discuss MUA’s strategies for presenting make-up on stage. The research uses qualitative methods, especially for the analysis of descriptive studies. The researcher collects the data by analyzing the makeup applied to the catwalk model. The treatments involve using reconstruction make-up. The results are that the catwalk model gets awesome makeup, especially on her eyes. The make-up stage helps cat walk models reduce their anxiety.